Trophic complexity alters the diversity–multifunctionality relationship in experimental grassland mesocosms. Issue 11 (31st March 2021) - Anujan, Krishna; Heilpern, Sebastian A.; Prager, Case M.; Weeks, Brian C.; Naeem, Shahid
Abstract: Plant diversity has a positive influence on the number of ecosystem functions maintained simultaneously by a community, or multifunctionality. While the presence of multiple trophic levels beyond plants, or trophic complexity, affects individual functions, the effect of trophic complexity on the diversity–multifunctionality relationship is less well known. To address this issue, we tested whether the independent or simultaneous manipulation of both plant diversity and trophic complexity impacted multifunctionality using a mesocosm experiment from Cedar Creek, Minnesota, USA. Our analyses revealed that neither plant diversity nor trophic complexity had significant effects on single functions, but trophic complexity altered the diversity–multifunctionality relationship in two key ways: It lowered the maximum strength of the diversity–multifunctionality effect, and it shifted the relationship between increasing diversity and multifunctionality from positive to negative at lower function thresholds. Our findings highlight the importance to account for interactions with higher trophic levels, as they can alter the biodiversity effect on multifunctionality. Abstract : We used a manipulated grassland mesocosm experiment to test the effects of higher trophic levels on ecosystem multifunctionality. We find that the number and identity of trophic levels affect the jack‐of‐all‐trades relationship between biodiversity and ecosystem multifunctionality. Our findings have implications in refining predictions for ecosystem multifunctionality in the face of ongoing biodiversity loss.